2009
DOI: 10.1038/sj.bjc.6605414
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor polymorphisms and prognosis of patients with epithelial ovarian cancer

Abstract: BACKGROUND: Recently, the vitamin D receptor (VDR) polymorphism FokI was shown to be associated with susceptibility to ovarian cancer. We aimed to examine whether VDR FokI polymorphisms influence the survivals of patients with epithelial ovarian cancer (EOC). METHODS: VDR polymorphisms from FokI in 101 patients with EOC were genotyped by sequencing. Overall survival was compared between FokI single nucleotide polymorphism using Kaplan -Meier survival curves with log-rank tests and the Cox proportional hazard m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 15 publications
2
26
1
Order By: Relevance
“…A recently conducted pooled analysis of five studies, including 1820 white non-Hispanic cases and 3479 controls, confirmed that the FokI T (f) allele is associated with ovarian cancer (Lurie et al, 2011). In addition, Tamez et al (2009) demonstrated that, in a Japanese population, the FokI CC (FF) genotype was associated with better survival compared to the CT (Ff) or TT (ff) genotypes (Tamez et al, 2009). …”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A recently conducted pooled analysis of five studies, including 1820 white non-Hispanic cases and 3479 controls, confirmed that the FokI T (f) allele is associated with ovarian cancer (Lurie et al, 2011). In addition, Tamez et al (2009) demonstrated that, in a Japanese population, the FokI CC (FF) genotype was associated with better survival compared to the CT (Ff) or TT (ff) genotypes (Tamez et al, 2009). …”
Section: Discussionmentioning
confidence: 85%
“…In recent years, the relevance of VDR polymorphisms as risk factors for the development of various types of cancer, including ovarian cancer, has been evaluated in numerous population studies (Lurie et al, 2007(Lurie et al, , 2011Clendenen et al, 2008;Kö stner et al, 2009;Tamez et al, 2009;Tworoger et al, 2009). However, these studies have demonstrated variable and inconsistent results (Lurie et al, 2007(Lurie et al, , 2011Clendenen et al, 2008;Tamez et al, 2009;Tworoger et al, 2009). Therefore, we aimed to study whether the FokI and BsmI SNPs situated in the VDR gene can be a genetic risk factor of ovarian cancer in the Polish population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one study involving ovarian cancer patients, the Fok1 C/C genotype was associated with a better prognosis than with the C/T and T/T genotypes (HR, 0.18; 95% CI, 0.05-0.61) [30]. The number of stars attributed to each domain is a measure of study validity.…”
Section: Vdr Expression and Relevant Polymorphismsmentioning
confidence: 99%
“…Recently, several studies reported that genetic variations of VDR were associated with progression and prognosis of common cancers [14][15][16][17][18][19][20] , including lung cancer [14,15] . Zhou et al reported that patients with variant genotypes of rs11568820 (GA/AA) had a longer survival time than those with GG genotype in early-stage lung squamous cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%